Experimental and simulation approaches for improving integrated circuit impedance characterisation under electrostatic discharge condition - Ding, Lik Suong (2021)
This study was conducted to produce an accurate macro model of an Integrated Circuit (IC) by means of experiment, to be implemented for any application, both in time domain and frequency domain analysis. A probe is designed and optimised to measure a multipin IC with different pin distance. The multipin IC characteristic impedance was experimentally measured using two probes, where the measured combinations of S-Parameter are combined using a self-written software to produce a complete S-Parameter representation of the IC. The S-Parameter file is not suitable for time domain analysis, because vector fitting is required for each simulation. The S-Parameter file is then converted to macro model with controlled accuracy level. The macro model is also ensured its passivity and causality by using commercial macro modelling software (IdEM). The macro model has shown good correlation between time domain and frequency domain analysis. The macro model was then exported as a SPICE model, and was implemented on an Advanced Driver Assistance Systems (ADAS) printed circuit board (PCB). Co-simulation was then performed on the PCB and the results are compared with the measurement results of the fabricated PCB. The SPICE model used in this simulation has shown good resonant frequency correlation between 91 % to 99 %. Finally, the PCB along with the SPICE model was simulated with an Electrostatic Discharge (ESD) gun to observe the current distribution. This research has produced a practical and accurate method, to accurately model an IC as a SPICE model. The SPICE model will help many engineers to improve the accuracy of the virtual prototyping, hence reducing the product’s time to market.